Free Fibula Flap for Extremity Oncologic Defects: Factors Influencing Union and Functional Outcomes. Issue 4 (9th December 2022) - Mericli, Alexander F.; Asaad, Malke; Lewis, Valerae O.; Lin, Patrick P.; Goodenough, Christopher J.; Adelman, David M.; Oates, Scott D.; Hanasono, Matthew M.
Abstract : Background: The goal of this study was to evaluate outcomes after vascularized bone flap (VBF) reconstruction of oncologic bony extremity defects. A secondary goal was to compare union rates based on various insetting methods, including onlay, intermedullary, and intercalary. Methods: The authors conducted a retrospective review of consecutive patients who received an extremity reconstruction with a fibula flap after oncologic resection between 2001 and 2019. Results: The authors identified a total of 60 fibular VBFs in 55 patients (67% lower extremity, 33% upper extremity). The overall union rate was 91.7% (55 of 60). For lower extremity reconstructions, the mean time to full weightbearing was 16 months (range, 4 to 44 months). Fibula VBFs were onlay in 65% of cases, intercalary in 23%, and intramedullary in 12%. Forty-three percent of patients required a reoperation as a result of a surgical complication. Immediate femur reconstruction subgroup analysis demonstrated that onlay fibula flap orientation was associated with a significantly increased risk for any complication (odds ratio, 6.3; 95% CI, 1.4 to 28.7; P = 0.03) as well as an increased risk for requiring conversion to endoprostheses because of nonunion (OR, 12.1; 90% CI, 1.03 to 143.5; P = 0.03) compared with intramedullary placement. Conclusions: The free vascularized fibula flap is a reliable option for functional reconstruction of any long bone extremity defect, but complications in these complex procedures are not uncommon. In patients with immediate femur reconstructions, intramedullary fibula placement was associated with significantly lower complication and lower metallic implant conversion rates and a trend toward a more rapid early union compared with onlay VBF. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.